Practice and progress : British sociology 1950-1980 - Abrams, Philip (Routledge library editions. British Sociological Association, 2018)
"Originally published in 1981 Practice and Progress is a collection examining the changes that have occurred in the theories, methodologies and practices of sociology, in the institutional and educational setting of the subject, and in British society. The themes pursued include the professionalization of sociology its development and standing in the universities; the impact on it of Marxism and feminism and the major debates over positivism and empiricism, quantitative methods, linguistic analysis; and numerous other crucial methodological and theoretical concerns."--